Pembinaan Literasi Finansial Usia Sekolah Dasar Melalui Program Mari Gemar Menabung - Syarifuddin; Andika Marzuki; Nursalim; Muhammad Ikhsan Sukaria; Awaluddin Bahar (Jurnal Abdi Masyarakat Pendidikan, 2026)
The community service program conducted at SD Inpres 10/73 Arallae, Kahu District, Bone Regency, involved socialization on financial literacy and the importance of saving from an early age through the “Let’s Love Saving” Program. The program aimed to foster students’ understanding and awareness of the importance of saving early in life. The implementation method used a participatory educational approach involving 30 students of SD Inpres 10/73 Arallae who actively participated in the financial literacy learning process. The activities were carried out through several stages, namely preparation, implementation, evaluation, and reporting. The results of the program showed that students were happy with the classroom saving program and were enthusiastic about participating in saving activities. The availability of supporting facilities was able to increase students’ interest and motivation to develop saving habits. Therefore, regular financial literacy education and continuous guidance are needed so that students can maintain enthusiasm for saving and apply a frugal and non-consumptive lifestyle in daily spending. Financial management should be taught from an early age with the expectation that students will be able to manage finances wisely and develop good character